Decay rate of gas-phase peracetic acid in a polyvinyl fluoride sample bag - Doepke, Amos; Streicher, Robert P; Stastny, Angela L (Environmental science--processes & impacts, 2025)
In this study the temperature dependent decay rate of gas-phase peracetic acid (PAA) concentrations in polyvinyl fluoride (PVF) sample bags was measured. Headspace from a PAA solution was used to dynamically generate atmospheres of gas-phase PAA which were transferred to PVF bags. The concentration of gas-phase PAA in PVF bags, in a temperature-controlled environment, was measured time using both selected ion flow-tube mass spectrometry (SIFT-MS) and impinger based colorimetric measurements. A review of PAA decomposition reactions, kinetics, and results of SIFT-MS measure of PAA and acetic acid are discussed. Gas-phase PAA concentrations in the PVF bags exhibited exponential decay consistent with first-order kinetics. The temperature dependent decay rate of gas-phase PAA concentration in PVF sample bags had half-lives that ranged from 19 h (at 30 °C) to 45 h (at 10 °C). From the Arrhenius equation, an activation energy of 34.2 ± 1.1 kJ mol (8.2 ± 0.3 kcal mol ) was calculated from the temperature dependence of the decay constant. In this work, the half-lives of gas-phase PAA concentrations measured in PVF were considerably longer than other studies of PAA in containers.